Pengembangan Media Pembelajaran Powerpoint Interaktif Materi Kuliner Thailand Mata Kuliah Kuliner Asia - Narayana, I Komang; Sukerti, Ni Wayan; Masdarini, Luh (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
This study aims to describe the development process of interactive PowerPoint learning media assisted by Canva in the Asian Cuisine course, particularly on Thai cuisine materials using the 4D model, and to determine the feasibility of the media based on validation by subject matter experts as well as media and instructional design experts. This research employed a Research and Development (R&D) approach with a descriptive quantitative method. Data were collected through questionnaires distributed to subject matter experts and media/design experts, and then analyzed descriptively in the form of percentages. The results show that the development process was carried out systematically in accordance with the 4D model, which includes: the Define stage to analyze learning needs; the Design stage to prepare content, create slides, and determine visual appearance; the Develop stage to produce the media and conduct expert validation; and the Disseminate stage to distribute the final product on a limited scale. Validation results indicate that the media falls into the highly feasible category, with a score of 97,14% from subject matter experts and an average score of 95.71% from media & design experts. Thus, the interactive PowerPoint media assisted by Canva developed in this study is proven to be highly feasible as an alternative learning medium in the Asian Cuisine course. This media can help students better understand the characteristics of Thai cuisine in a more engaging, applicable, and contextual manner.